Corticosteroid in Septic Shock: Advantage or Disadvantage? - Sakura Muhammad Tola (Majalah Sainstekes, 2019)
Sepsis has become a major health issue, with more patients dying in hospitals due to sepsis related complications. The pathogenesis of sepsis is complex and involves multiple aspects of the interaction between the infecting microorganisms and the host. Sepsis is fundamentally an inflammatory disease mediated by the activation of the innate immune system. In the case, sepsis is an unbalanced (proinflammatory and anti-inflammatory), dysregulated response, the localized process goes out of control and becomes systemic contribute to diminished oxygen delivery. The process also leads to decreased hemodynamic stability, hyperglycemia and ultimately, multi organ dysfunction syndrome and death in septic shock. The use of corticosteroid hydrocortisone as adjunctive therapy is still debating due to the lack of supporting study and differences result among the studies.